Neoliberalism and territorial governance: proposals and reflections based on the case of Chile - Bustos Gallardo, Beatriz; Lukas, Michael; Stamm, Caroline; Torre, André (Revista de Geografía Norte Grande, 2020)
The paper analizes governance and its new mechanisms from the perspective of the spatial political economy for the case of Chile, examining three key dimensions» the context and its socio-political projects, the dispositifs (devices) of territorialization and re-scaling, and, the techniques, practices and tools of territorial intervention. After a theoretical and contextual review, the paper discusses two cases of territorial governance : the Salmon Task Force (Los Lagos Region) and CREO Antofagasta (Antofagasta Region), showing that these mechanisms are not created to solve the core problems of the neoliberal project, or to rethink in a collective manner the territories, but, to give continuity to the prevailing more of production and to restore legitimacy to extractive sectors and firms in times of crises. The paper concludes arguing the need to move away from a neutral understanding of governance toward a critical understanding that considers the context and power relations.